Cultures of plague medical thinking at the end of the Renaissance - Cohn, Samuel Kline (Oxford University Press, 2010)
This title highlights the impact that the plague epidemic in Italy between 1575 and 1578 had on the medical writers and practitioners of the time. He asserts that these writers anticipated modern epidemiology and created the structure for plague classics of the next century.